PENERAPAN SANKSI PIDANA TERHADAP ANGGOTA SATUAN POLISI PAMONGPRAJA YANG MELAKUKAN TINDAK PIDANA KEKERASAN TERHADAP PEDAGANG KAKI LIMA DI WILAYAHKOTA PEKANBARU - Indah Tri Wahyuni; Dessy Artina; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The Civil Service Police Unit is a regional government tool in providing peace and public orderand enforcing regional regulations. In addition, the civil service police unit can also carry out publicwelfare and provide the best service to the public, the civil service police unit requires certain powers to actaccording to their own initiatives and policies, especially in urgent circumstances and where there are norelevant regulations.This study is a sociological juridical research that is a type of research to see the effectiveness ofthe law in the field in accordance with the reality of life in society. This research was conducted at thePekanbaru City Police Department on the grounds that there were still many members of the Satpol PP whocommitted violent crimes against the street vendor. While the population and sample are parties related tothe problems examined in this study, the data sources used, primary data, secondary data, and tertiary data.The technique of collecting data in this study was by interviews, questionnaires and literature review.From the results of the research the authors concluded, first the application of criminal sanctionsto members of the civil service police unit who committed violations where the apparatus only gavesanctions in the form of reprimand, and in this case the sanctions given by the apparatus were certainly noteffective and not in accordance there is. Second. Sanctions that should or ideally be given to members of thecivil service police unit who commit a crime of violence are in accordance with Article 351 of the CriminalCode concerning Persecution, namely imprisonment and criminal penalties and Discipline Sanctions givenby the agency of the Civil Service Police.Keywords: Application of Sanctions - Civil Service Police - Violent Crimes.